IBM Power Systems Infrastructure I/O for SAP Applications - Quintero, Dino; Haefele, Edmund; Kehrer, Gerd; Probst, Katharina (IBM Redbooks, 2020)
This IBM® Redpaper publication describes practical experiences to run SAP workloads to take advantage of IBM Power Systems I/O capabilities. With IBM POWER® processor-based servers, you have the flexibility to fit seamlessly new applications and workloads into a single data center, and even consolidate them into a single server. This approach highlights all viable options and describes the pros and cons of each one to select the correct option for a specific data center. The target audiences of this book are architects, IT specialists, and systems administrators deploying SAP workloads, who spend much time and effort managing, provisioning, and monitoring SAP software systems and landscapes on IBM Power Systems servers.